Profile of prescription drugs for institutionalized elderly (Research, Society and Development, 2020)
Objectives: to describe and quantify the medications most used by residents of this institution, to evaluate the prevalent morbidities, as well as to verify the use of medications potentially inappropriate for the elderly. Methods: This is an epidemiological, descriptive, cross-sectional study, and the data were obtained from the analysis of the medical records of 56 elderly residents. Results: the most used drugs were those with action on the cardiovascular system (85.71%), followed by those acting on the central nervous system (69.64%), thus evidencing that the prevalent diseases are associated with the cardiovascular system followed by those that affect the nervous system. The use of drugs that are classified as inappropriate drugs for the elderly was also demonstrated. Conclusion: this study demonstrated that the nosological profile of the residents of the studied institution corresponds with the profile of the elderly Brazilian asylum, in addition it demonstrated the presence of polypharmacy and that among the drugs used are those classified as potentially inappropriate for the elderly. Thus, results demonstrate a worrying fact, since polypharmacy and the use of inappropriate medications can result in iatrogenesis, thus directly affecting the health of the elderly.